2013
DOI: 10.1038/bjc.2013.462
|View full text |Cite
|
Sign up to set email alerts
|

External validation of an online nomogram in patients undergoing radical nephroureterectomy for upper urinary tract urothelial carcinoma

Abstract: Background:The objective was to validate an online nomogram developed based on the French collaborative national database on upper urinary tract urothelial carcinoma (UUT-UC) using a different cohort.Methods:The study comprised 328 patients with UUT-UC who underwent radical nephroureterectomy. The discrimination of models was quantified using Harrell's concordance index. The relationship between the model-derived and actuarial cancer-specific mortality was graphically explored within calibration plots. Calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
(40 reference statements)
0
27
1
Order By: Relevance
“…In UTUC, specific mortality after RNU mainly depends on pathologic features [2,3,5]. The combination of prognostic variables may improve predictions of oncologic outcomes [2,7]. Nevertheless, the duration of survivorship after initial surgery that is one important predictive factor of subsequent survival remains excluded from most multivariate analyses [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In UTUC, specific mortality after RNU mainly depends on pathologic features [2,3,5]. The combination of prognostic variables may improve predictions of oncologic outcomes [2,7]. Nevertheless, the duration of survivorship after initial surgery that is one important predictive factor of subsequent survival remains excluded from most multivariate analyses [19].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, 5-yr relative survival statistics are often used to measure cancer control and to assess international comparisons. Nomograms have been built to integrate all independent covariables and thus to better individualise patient prognosis [2,7]. Nevertheless, probabilities of disease recurrence and death evolve over time and decrease with increased survivorship.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of UTUCs are invasive at diagnosis, compared with 15-25% of all bladder tumors, and thus this disease has a comparatively poor prognosis (6). The European Association of Urology Guidelines reviewed several published studies and reported that four different nomograms are available for predicting survival rates postoperatively, based on standard pathological features (17)(18)(19)(20). Recently, several papers reported a number of clinicopathological features and gene promoter methylation statuses of UTUC patients that might affect the probability of bladder recurrence, including patient gender, smoking status, tumor multifocality, surgical management, and GDF15 and RASSF1A promoter methylation (11,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, 3‐5‐year relative survival statistics are often used to measure cancer control and assess international comparisons . Nomograms have been built to integrate independent prognostic variables to better individualize and predict patient prognosis . Initial cancer prognosis assessment at surgery helps to select post‐RNU therapy and follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rarity of UTUC and different surgical techniques with heterogenous patient cohorts, it is difficult to acquire sufficient data to explore characteristics of patients with UTUC. A nomogram was developed from Western UTUC cohorts, and the few Asian patient‐based nomograms have incorporated small cohorts of patients . Therefore, the aim of the current study was to determine a prediction model of DFS and OS of UTUC after RNU using a large, multicenter, Korean cohort, and to validate the nomogram model.…”
Section: Introductionmentioning
confidence: 99%